Read about the political and law effects of the Corona pandemic on the global system - Dr.Nour Ali Sekeb; Dr. Muhammad Amer Al-Saeedi (The college of law and political science journal, 2023)
The Corona virus was considered a global pandemic based on the World Health Organization's declaration on March 11, 2020, as it announced that the outbreak of the new "Corona" virus, which causes the "Covid-19" disease, had reached the levels of a global pandemic. In a number of countries, an outbreak has been detected The disease resulted from deficiencies in the public health and social care systems, which made it difficult to protect vulnerable populations and reduce disease transmission.In response to this crisis, governments have worked to prioritize everyone's right to health, and for fear of the rapid spread of the epidemic, home quarantine has been imposed, with which more than 90 countries have worked. These measures have not been accompanied by economic and social policies that can reduce the burdens and consequences, which It led to political and legal effects, which we will try to address in the research by answering a number of questions that will be raised. It was discussed in two sections. In the first section, we dealt with the political effects, and in the second section, the legal effects.